Solubility And Dissolution Enhancement of Budesonide by Solid Dispersion Using Rotary Evaporation Technique - Ajit B Patil,; Aishwarya Jadhav,; Afaque Ansari,; Rushabh Jain,; Yogesh Darade,; Shraddha Birajdar, (International Journal of Scientific Research in Science and Technology, 2024)
The Purpose of the work was to enhance the solubility and dissolution of Budesonide API Powder which was under BCS Class 2 system. Solid dispersion of Budesonide were prepared by using different polymers like Poly vinyl pyrrolidone (PVP K30), polyethylene glycol 6000 (PEG6000) by using Solvent Evaporation Method by using Rotary Evaporator, in the 1:1:1, 1:1:2, 1:1:3, 1:2:1, ratios of drug and carrier. The In-vitro release profile of all solid dispersions (F1 to F9) were comparatively evaluated and also studied against pure Budesonide. The evaluation test were carried out like drug content, solubility, drug release studies. The drug and polymer interaction was studied by using Fourier Transport Infra-Red and Differential Scanning Calorimetry, Powder X Ray Diffraction studies were also carried out to find out the Crystalinity of Solid Dispersion, SEM was carried out for study of surface morphology.
Keywords: Occupational Structure; Agriculture Sector; Non-Agriculture Sector; Workers; Non Workers; Kerala